Antifungal Activity and Biocompatibility of α-AgVO3, α-Ag2WO4, and β-Ag2MoO4 Using a Three-Dimensional Coculture Model of the Oral Mucosa - Pimentel, Bruna Natália Alves da Silva; Marin-Dett, Freddy Humberto; Assis, Marcelo; Barbugli, Paula Aboud; Longo, Elson; Vergani, Carlos Eduardo (Frontiers in Bioengineering and Biotechnology, 2022)
Fungal infections have become a major concern in the medical community, especially those caused by Candida spp. Within this species, Candida albicans stands out for being an opportunistic commensal fungus that can cause superficial and invasive infections. Current antifungal therapy involves the local and/or systemic use of drugs such as azoles, polyenes, and echinocandins. These antifungals are based on highly specific target sites and the development of resistance may occur with changes in the enzymatic pathways which serve as the drug targets. Thus, the development of new antifungal drugs is highly recommended to prevent drug resistance. The present investigation evaluated the antifungal activity of silver-containing microcrystals such as silver vanadate (α-AgVO3), silver tungstate (α-Ag2WO4), and silver molybdate (β-Ag2MoO4). In addition to having antimicrobial activity, such compounds should not cause damage to underlying tissues. Thus, to better assess the biocompatibility of new compounds, a new 3D co-culture model involving three cell lines was developed. The validation of the model was based on fluorescent markers and confocal laser microscopy. The biocompatibility of silver-containing microcrystals was evaluated by MTT assay. 3D co-culture was infected with C. albicans biofilm and challenged with α-AgVO3, α-Ag2WO4, and β-Ag2MoO4. The action of microcrystals on C. albicans biofilm was evaluated by colony forming units (CFU/mL) and live/dead staining. In addition, production of proinflammatory cytokines IL-6, IL-8, IL-1β, and TNFα was measured by cytometric bead array (CBA) kit using the flow cytometry. The 3D co-culture model described here proved to be adequate to assess both the biocompatibility of the new materials and the infectious processes. Regarding the biocompatibility of the microcrystals, only α-AgVO3 [15.62 µg/mL] showed a decrease in cell viability. The anti-biofilm activity of α-Ag2WO4 was similar to that of the standard drug (fluconazole). Although α-Ag2WO4 was able to induce the production of IL-6, IL-8, and IL-1β, no differences in cytokine production were observed between noninfected and infected models treated with this microcrystal. β-Ag2MoO4 inhibit the production of TNFα in the infected model, however, it showed no antibiofilm activity. Based on the biocompatibility and antifungal findings, α-Ag2WO4 is a promising material for treating C. albicans infection.